Characteristics of oxide scale formed on Cu-bearing austenitic stainless steel during early stages of high temperature oxidation - Swaminathan, Srinivasan; Krishna, Nanda Gopala; Kim, Dong-Ik (ELSEVIER, 2015)
Oxide scale evolution on Cu-bearing austenitic stainless steel 304H at 650 degrees C, in ambient air, for exposure times 100, 300, 500 and 1000 h, has been investigated. Surface morphology and chemistry of the oxide scale grown were examined using SEM/EDX and XPS. The oxidation kinetics was determined by measuring the weight change using an electronic balance. At the initial stage, up to 500 h of exposure time, the oxidation rate was rapid due to surface reactions governed primarily by oxygen ingress, and then, dropped to a low rate after prolonged oxidation for 1000 h. The diffusion of reactants through the initially formed oxide scale limits the oxidation rate at longer times, thus, the progress of reaction followed the parabolic kinetics. The formed oxide scale was enriched significantly with segregation and subsequent oxidation of Nb, and finely dispersed metallic Cu particles. Within the time frame of oxidation, the oxide scale was mainly composed of mixed oxides such as FeCr2O4 and MnCr2O4 along with the binary oxides of Fe, Cr and Mn. Moreover, the precipitation fraction of Cu-rich particles on the oxide scale increased markedly with increase of exposure times. The chemical heterogeneity of oxide scale suggests that the oxidation occurred in a non-selective manner. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: BEHAVIOR; CORROSION; TERNARY; TENSILE; ALLOYS; XPS; FE